2013
DOI: 10.1038/lsa.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-thin, planar, Babinet-inverted plasmonic metalenses

Abstract: We experimentally demonstrate the focusing of visible light with ultra-thin, planar metasurfaces made of concentrically perforated, 30-nm-thick gold films. The perforated nano-voids-Babinet-inverted (complementary) nano-antennas-create discrete phase shifts and form a desired wavefront of cross-polarized, scattered light. The signal-to-noise ratio in our complementary nano-antenna design is at least one order of magnitude higher than in previous metallic nano-antenna designs. We first study our proof-of-concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
423
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 616 publications
(427 citation statements)
references
References 23 publications
0
423
3
1
Order By: Relevance
“…This result even significantly outperforms (by an order of magnitude) the recently demonstrated extreme short focusing using transmitarrays of optical antennas, 39,40 which reported a best case of f/D50.625 (2.5 mm/4 mm) at l 0 5676 nm. 40 There are several parameters that determine the operation of the device, primarily the effective permittivity z' , x' f g, the tilt angle a and the thickness. These parameters determine the location of the focal spot with respect to the exit facet as well as the strength of the focus.…”
Section: Short Focal Distancementioning
confidence: 70%
See 2 more Smart Citations
“…This result even significantly outperforms (by an order of magnitude) the recently demonstrated extreme short focusing using transmitarrays of optical antennas, 39,40 which reported a best case of f/D50.625 (2.5 mm/4 mm) at l 0 5676 nm. 40 There are several parameters that determine the operation of the device, primarily the effective permittivity z' , x' f g, the tilt angle a and the thickness. These parameters determine the location of the focal spot with respect to the exit facet as well as the strength of the focus.…”
Section: Short Focal Distancementioning
confidence: 70%
“…It is shown that such a device can in fact outperform thick lenses with very low f/D ratios, to create areas of high power concentration very close to the exit facet of the device, i.e., at short focal distances. It also outperforms the recently reported flat and thin lenses realized using arrays of optical antennas 39,40 in terms of their f/D ratios. The proposed focusing hetero-junction device is an alternative method for extremely close power concentration under normal incidence.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Metasurfaces have also been proposed to implement metalenses working in different bands [7][8][9][10]. Near-infrared metalenses and axicons have been proposed at λ ∼ 1.5 µm [7,8] and 1 THz [10].…”
Section: Introductionmentioning
confidence: 99%
“…Metasurfaces comprised of nanoantenna phased-array have been investigated for holography, quarter-waveplate, metalenses, and meta-mirrors [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%